On the Critical Speed, Supercritical Bifurcation, and Stability Problems of Certain Type of High-Speed Rail Vehicle - Hao Dong; Qunsheng Wang (Shock and Vibration)
Recently, Chinese engineers have proposed a simple way to find the vehicles’ critical speed, which is similar to the ramping method. In this article, through an example of vehicle of supercritical properties, it is proved that the new easier way is not scientifically justified and should not be used in engineering practice. In addition, the ramping way also yields inaccurate critical speed. Then one abnormal vibration phenomenon which appears on Beijing-Shanghai high-speed line is studied. The results demonstrate that it is car body hunting but not bogie hunting. Finally, through the computation and comparison of the lateral ride indices under different conditions, one stability problem about stochastic limit cycle banding is tentatively discussed.